Perbedaan Tanaman Kacang Hijau Dan Jagung Di Tempat Terang Dan Gelap - Harita, Reza Septa; Bernardus Zebua; Gulo, Zefri Wiliam; Richardo Harefa; Sastra Alberta Hia (CV. SINAR HOWUHOWU, 2025)
This study investigates the growth differences between maize (Zea mays) and mung bean (Vigna radiata) when cultivated under light and dark conditions. The research aimed to understand the influence of light availability on the germination and early growth stages of these plants. A controlled experiment was conducted where both plants were grown under two conditions: full light exposure and complete darkness. Key growth parameters, including stem length, leaf development, and overall health, were measured over a set period. The results showed significant differences in growth patterns. Maize exhibited better growth under light conditions, with robust stem development and larger leaves, while mung beans demonstrated some adaptability to dark conditions, though with elongated stems and weaker structural integrity. These findings emphasize the role of light in plant growth and highlight species-specific adaptations to environmental conditions. This research provides insights into optimizing growth strategies for these crops in varying agricultural settings.